The Utilization of Facebook During Covid-19 Pandemic by First-Year College Students - Boholano, Helen B.; Cajes, Roberto (International Journal of Social Learning (IJSL), 2021)
Facebook is one of the popular social networking sites used by students. First-year college students who have primarily engaged themselves in Facebook are being influenced and affected by such media platforms. Students who use Facebook frequently are likely influenced by other people. On the other hand, their studies can likely be distracted. Instead of spending their time reviewing their school lessons, students get tempted to allot much of their time using Facebook. This study determined the reasons and feedback of first-year college students using Facebook. This research using a mixed method of quantitative and qualitative in interpreting and analyzing the data. The respondents were the first-year college students of Cebu Normal University, Cebu City. Findings revealed that using Facebook may cause adverse effects on students' academic performance due to frequent use of such media. However, Howeverebook can also bring positive effects to the students' academic performance. As a communication tool, Facebook provides information and acquiring knowledge from the different Facebook users. Facebook is beneficial in their studies. Through Facebook, college students can now share and exchange information through brainstorming and collaborating in the Group Chat. Therefore, the utilization of Facebook in learning as a tool in instruction during the Covid-19 pandemic is beneficial to learners and lecturers.